PERBANDINGAN PERAMALAN HOLT DOUBLE EXPONENTIAL SMOOTHING, HOLT WINTER TRIPLE EXPONENTIAL SMOOTHING, DAN ARIMA (Studi Kasus : Frekuensi Transaksi Agen Brilink, PT Bank Rakyat Indonesia) - Dinda Parwita Aulia Nofri (2023)
People's need for services from banks is quite increasing. PT Bank Rakyat Indonesia Tbk developed the Brilink program as an expansion of BRI services to serve banking transactions in real time. Therefore, the increasing number of Brilink transactions from time to time, it can be said that this program is very helpful to the community so that PT Bank Rakyat Indonesia Tbk continues to develop this program. In addition to looking at historical data and current data on the frequency of transactions, forecasting data is also needed as one of the considerations for Brilink development planning. Based on the explanation above, forecasting research was carried out using the Holt Double Exponential Smoothing (HDES), Holt Winter Triple Exponential Smoothing (HWTES), and ARIMA methods. As a result of this study, it was found that the HDES model of α and β parameters of 0,3 0,4 and 0,3 0,3 resulted in a MAPE of 4,704% and 4,810%, the HWTES Additive model of α, β, and γ parameters of 0,9 0,1 0,6 and 0,1 0,1 0,6 with a MAPE of 5,622 % and 5,894%, and the ARIMA model (0,1,1) and ARIMA(1,1,1) produced a MAPE of 4,804% and 5,886%. So that Holt Double Exponential Smoothing with α and β parameters of 0,3 0,4 and ARIMA (0,1,1) is the best model in this study. From the forecasting results, the number of Brilink transaction frequencies continues to increase so that PT Bank Rakyat Indonesia Tbk can develop Brilink services, increase their effectiveness, expand Brilink agents, & prevent adverse events that can happen to agents.